Sponsoring und Doping - Beendigung von Sponsoringverträgen wegen Verfehlungen des Gesponserten, insbesondere in Dopingfällen - Schaub, Renate (Universitätsverlag Göttingen, 2008)
The increased detection of doping in professional sports has led to a strengthening of the discussion on the legal aspects of doping. So far criminal and/ or verbandsrechtliche questions were the focus. For example the question of whether and how sponsorship contracts may be terminated in cases of misconduct of the sponsored. First, it examines how appropriate cancellation clauses could be like. Second, consider the conditions under which, even without explicit rules for doping a termination in accordance with general principles of contract law is concerned. It also discusses the legal consequences of termination, and in particular its relationship to other contractual consequences of doping, such as claims for damages or penalties.